2018
DOI: 10.3899/jrheum.170500
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Self-reported Patient Experiences: Insights from Digital Patient Communities in Psoriatic Arthritis

Abstract: Objective.To evaluate the types of experiences and treatment access challenges of patients with psoriatic arthritis (PsA) using self-reported online narratives.Methods.English-language patient narratives reported between January 2010 and May 2016 were collected from 31 online sources (general health social networking sites, disease-focused patient forums, treatment reviews, general health forums, mainstream social media sites) for analysis of functional impairment and 40 online sources for assessment of barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…This study found that symptoms related to musculoskeletal pain were the most bothersome symptoms of PsA, compared with psoriasis-related symptoms, in rheumatology-focused patients with overall low skin disease severity. This finding mirrors other patient impact studies in PsA [3,16,28,29], and patients and rheumatologists are generally in agreement that joint pain is the most burdensome symptom of PsA [30]. However, our findings also highlight other interesting trends.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study found that symptoms related to musculoskeletal pain were the most bothersome symptoms of PsA, compared with psoriasis-related symptoms, in rheumatology-focused patients with overall low skin disease severity. This finding mirrors other patient impact studies in PsA [3,16,28,29], and patients and rheumatologists are generally in agreement that joint pain is the most burdensome symptom of PsA [30]. However, our findings also highlight other interesting trends.…”
Section: Discussionsupporting
confidence: 90%
“…Multiple studies have found discrepancies between physicians' understanding of disease burdens and the actual burdens felt by patients [30,34]. Some of this disconnect may stem from the use of patient-reported outcome measures that fail to account for all symptoms and impacts [29]. Ensuring that clinicians and researchers fully understand the burden of symptoms on patients is key to better When probing patient treatment preferences, respondents in this study most strongly desired an improvement in function and joint symptoms, which is reflected in the findings of other studies [5,16].…”
Section: Discussionmentioning
confidence: 99%
“…PROs reflect many important issues that significantly impact patients with PsA, including challenges in mental, physical, and social functioning, pain, fatigue, work-related disability, in addition to psoriatic, axial, and skin disease symptoms. Many of these symptoms and sequelae of disease are represented by the core domains recommended by the GRAPPA-OMERACT working group to be measured in all RCTs to evaluate treatment efficacy [2,3,18,[37][38][39][40]. In a recent qualitative interview study of PsA patients recruited through the FORWARD databank, joint pain and stiffness, skin symptoms, fatigue, and physical disability were identified as some of the most salient PsA symptoms [39].…”
Section: Discussionmentioning
confidence: 99%
“…PsA impacts physical functioning, daily activities, emotional well-being, and health-related quality of life (QoL) [ 6 ]. Although the most impactful symptoms include pain, stiffness, swelling, fatigue, sleep disturbances, and physical disability [ 7 - 9 ], they often go untreated because of diagnosis delays and barriers to accessing care [ 6 , 10 ].…”
Section: Introductionmentioning
confidence: 99%